(untitled) (African Journal of Biomedical Research, 2019)
Abuse of antibiotics through self-treatment is of public health concern, especially in rural communities of low income countries. This study evaluates the prevalence of self-medication with five broad spectrum antibiotics (ampiclox, amoxillin, co-trimoxazole, metronidazole and tetracycline) commonly used to treat infections among non-health workers living in rural communities in Kano, Nigeria. A cross-sectional survey of 300 randomly selected adult villagers was conducted with self-administered questionnaire. The prevalence of self-medication with at least one of the antibiotics was 70.3%. The most self-medicated antibiotic is ampiclox followed by tetracycline, amoxicillin, co-trimoxazole and metronidazole. Over 50% of the respondents purchased substandard antibiotics, which cost between 0.1-0.5 per dose from illegal drugs sellers in their communities. While only 29 respondents ever completed the dosage of the self-medicated antibiotics, about 22% took the antibiotics for 2 days and 41% took only 1 dose. A total of 154 (51.3%) self-used tetracycline and metronidazole for treating diarrhea, while 30.6% and 62% used ampiclox and amoxicillin to treat undiagnosed urinary tract infections and typhoid fever respectively. Only 33% have used antibiotics previously prescribed by health care workers, but the majority used them as a result of family and friends’ recommendations. Surprisingly, only 19 out of 300 believed that self-medication is a problem, but the majority (168) has contrary believe and 35 have no idea. Self-medication with five commonly used broad spectrum antibiotics is very high in rural communities and will require the development of a viable antibiotic stewardship programs to arrest the situation.